Implementasi Cyber Public Relations pada Instagram @dcikabakery - Atika Suri; Sadiyah El Adawiyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Researchers will examine whether Cyber Public Relations activities are effective in improving the D’cika Cakes & Bakery brand. The aim is to analyze the use of social media as an information medium for D'cika Cakes & Bakery in Cyber Public Relations activities referring to Chris Heuer's theory with four indicators, namely context, communication, collaboration and connection. This research was conducted using a qualitative approach with descriptive methods and using interviews and observation as data collection techniques. D'Cika uses various promotional media, including social media, television, digital platforms and billboards, to market its products or services. They specialize in business-to-business marketing communications and are directly involved in B2C activities. D'cika has two accounts, @dcikabakery.official and @dcikabakery, which are managed by the marketing communications team. The brand owner and marketing team have full control over the selection of promotional media. D'Cika Cakes & Bakery uses Instagram to maintain its reputation, utilizing various promotional media such as advertising, public relations and digital marketing. Brand owners and marketing teams control media selection, ensuring product quality and customer satisfaction.